Causal Relationship of Branding, Integrated Marketing Communication, School Image and Parents’ loyalty to Regular Private Schools in the Upper Northern Region of Thailand. - Tangrapeeleart, Wathit; Wingwon, Boonthawan; Bunmark, Jamnian (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
The purposes of this research were (1) to study the importance of branding, integrated marketing communications, school image and parents’ loyalty. (2) to study causal relationship of branding, integrated marketing communications, school image and loyalty. and (3) to find the structural equation model of parents’ loyalty to private schools in the upper northern region of Thailand. The samples were collected from the parents having two or more children 8 private schools of 350 in the upper northern region of Thailand, such as Maehokson Chiangrai, Phayao, Chiangmai, Lamphun, Lampang, Phare and Nan. The data conducted by questionnaires and in-depth interview techniques. Quantitative data was analyzed by descriptive statistics, included frequency, percentage, standard deviation, as well as factor analysis, and structural equation modeling SEM and use the Amos program The research results shows that respondents rate the highest priority on parental loyalty, followed by school image, branding and integrated marketing communication at a high level in all factors. The results of causal relationships by using structural equations and analyzing the influence variables. It was found that integrated marketing communication influenced the brand and the brand had the most influence on integrated marketing communication. Follow was the image of the school, which had an influence on the loyalty of the parents and the brand, had an influence on the image of the school. Lastly, integrated marketing communication influences the image of the school. The results of this research will be useful for private school administrators to determine marketing strategies or find ways to use integrated marketing communications tools which can be appropriate to the situation and truly reach the school parents which will lead to loyalty to the organization.